Zika virus: Epidemiology, Pathophysiology, Clinical Manifestations, Diagnosis, and Prevention- A Challenge for India. - Naveen Kumar B.,; Asief M.,; Qadrie ZL, (International Journal of Pharma and Bio Sciences, 2023)
This study aimed to assimilate findings related to the Zika virus from the scientific literature. Zika virus (ZIKV) is an emerging pathogen of huge public health significance to human beings. The recent outbreak has been associated with the increased incidence of congenital anomalies such as microcephaly & Guillain-Barre syndrome (GBS). In this review, we address the current concern with context to India. There is also a need to look for any such animal cycle/sylvatic involvement in India. The recently detected four cases in India show local transmission of ZIKV, suggesting that ZIKV might have been present in India for a long time. Therefore, ZIKAV might become a major public health concern in the future. Several entry and adhesion factors enable infection, and cellular autophagy, which is needed for flaviviral replication. Transmission is by an infected mosquito during a blood meal. ZIKAV is also transmitted via congenital, perinatal, and sexual, possibly by blood transfusion, animal bite, and intrauterine transmission. Transmission via breastfeeding has yet to be reported. The incubation period from mosquito bite to symptom commencement is 3-12 days. Infection is likely subclinical in 80% of cases. Symptoms that last for two to seven days include fever, conjunctivitis, arthralgia, myalgia, and pervasive rash, which may be itchy. Headache, retro-orbital pain, peripheral edema, and gastrointestinal struggle have also been witnessed. The symptoms and clinical signs do not have good positive or negative predictive value. Laboratory testing includes polymerase chain reaction (PCR) of ZIKAV RNA. There was neither vaccine against ZIKAV nor antiviral for managing ZIKAV in India. Treatment is suggestive. The review provides scientific evidence for public policy care, planning, and implementation.